Strategi Pastoral Gereja Keuskupan Ruteng Dalam Menanggapi Politik Patronase: Sebuah Tinjauan Berdasarkan Teologi Publik - Pryatno, Emanuel Rizan (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2025)
This research examines the pastoral strategy of the Diocese of Ruteng Church in responding to the rise of patronage politics in the Manggarai region post-reformation. Using a public theology approach, the objective of this research is to analyze how the Church voices ethical and faith-based values amidst a corrupt local political context. Through a qualitative literature review method that examines official Church documents such as pastoral letters and synod documents, it was found that the Church's involvement has thus far been more educational-moral in nature. This strategy is realized through practical efforts such as public animation to cultivate a culture of shame and honesty, the radicalization of ethical attitudes through education and anti-money politics campaigns, and urging democratic institutions to operate fairly. Although this effort is an important public contribution, the research concludes that this approach has not yet effectively addressed the structural roots of patronage politics. Therefore, it is recommended that the Church deepens its involvement by integrating its moral and spiritual approach with more focused structural advocacy and cross-sectoral collaboration to realize a more holistic social change and a dignified democracy.